Resource dependence and enterprise ESG performance: an empirical study based on A-share listed companies - Fei, Yingqun; Fang, Lifeng; Luo, Zhejun; Liang, Wenjing (Frontiers in Ecology and Evolution, 2024)
The impact of resource dependence on social economy and environment lacks empirical evidence at the micro level. This paper uses the data of A -share listed companies from 2011 to 2020 to empirically test the impact of resource dependence on corporate ESG performance. We find that the corporate ESG scores in regions with high resource dependence will decline, and this conclusion still holds after robustness tests. Further analysis indicates that there are differences in the effect of resource dependence on enterprises sub-scores, with a significant negative impact on the environmental dimension and social dimension, and no significant impact on the governance dimension. It has a greater impact on the ESG score of SOEs and has no significant impact on non-SOEs. The empirical results of this paper enrich the research on the influencing factors of enterprise ESG performance, and further expand the research framework of the socio-economic consequences of enterprise resource dependence.